Computational discrete mathematics : combinatorics and graph theory with Mathematica - Pemmaraju, Sriram V., 1966-; Skiena, Steven S. (Cambridge, U.K. ; New York : Cambridge University Press, 2003)
With examples of all 450 functions in action plus tutorial text on the mathematics, this book is the definitive guide to Experimenting with Combinatorica, a widely used software package for teaching and research in discrete mathematics.
Includes bibliographical references (p. 448-457) and index.
oif 20/08/15
Loan
Keywords: Combinatorica (Computer file); Combinatorial analysis -- Data processing; Graph theory -- Data processing